Technical Control And Prevention Of Electrical Safety Hazards In Enterprises (Texas Journal of Multidisciplinary Studies, 2024)
This article discusses the control and supply of production processes through electric currents, which is a characteristic feature of living organisms. As a result, living cells in the human body vibrate due to rapid muscle contractions, which are primarily caused by disruptions in bioelectrical processes. The human body is primarily controlled by bioelectrical currents. This is caused by the effect of high-voltage electric current from the external environment, which disrupts the regulation of bioelectric currents. As a result, an electric shock occurs in the human body, leading to disturbances in the respiratory system and failure of the circulatory system